1979
DOI: 10.1111/j.1398-9995.1979.tb02006.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Bee Sting Hypersensitivity

Abstract: Fifty-six patients with serologically confirmed bee sting hypersensitivity were treated for 1-3 years with either bee venom (BV) (31 patients) or wholebody extract (WBE) (25 per cent of re-exposed patients on BV-therapy showed a diminished reaction and 75% no reaction. Thirty-three per cent of re-exposed patients on WBE-therapy developed an unchanged or worse reaction, 42% a diminished reaction and 25% no reaction at all. An initial rise in BV-specific IgE was observed in BV-treated patients, whereas IgE level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 18 publications
1
49
0
3
Order By: Relevance
“…Graft 1984, 73 Hunt 1978, 28 Müller 1979, 74 Schuberth 1983, 75 Thurneer 1983, 49 Tsicopoulos 1988, 76 Wyss 1993, 77 Yunginger 1979 78 a Brown 2003, 79 Hunt 1978, 28 Schuberth 1983, 75 Valentine 1990 Studies using standardised venom extract in any form of immunotherapy (subcutaneous or sublingual) were included. All appropriate allergens were included at all doses and all durations of treatment.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Graft 1984, 73 Hunt 1978, 28 Müller 1979, 74 Schuberth 1983, 75 Thurneer 1983, 49 Tsicopoulos 1988, 76 Wyss 1993, 77 Yunginger 1979 78 a Brown 2003, 79 Hunt 1978, 28 Schuberth 1983, 75 Valentine 1990 Studies using standardised venom extract in any form of immunotherapy (subcutaneous or sublingual) were included. All appropriate allergens were included at all doses and all durations of treatment.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Some studies investigated the effective amounts of single venom allergens, which suggested 3 µg for Dol a 5 and Dol m 5 respectively from Dolichovespula arenaria and Dolichovespula maculata, 5 µg for Ves g 5 from Vespula germanica, and in 12 µg for Api m 1 from Apis mellifera [30,31].…”
Section: Hymenoptera Venommentioning
confidence: 99%
“…Complete protection following VIT has been described in 75 to over 90% of patients (37, 57, 65). However, treatment failures have been reported in most studies (25,341,46,57,65,69). In the "Insect Venom Group of the Arbeitsgemeinschaft Dermatologische Forschung", 41 treatment failures were observed, 36 patients were allergic to bee venom and five to vespid venoms (Rzany, personal communication).…”
Section: Efficacy Of Venom Immunotherapymentioning
confidence: 99%
“…All endeavour to obtain satisfactory protection in the majority, minimize side effects, and optimize convenience for the patients. Rush protocols (11,57,59,82,86,88,90) usually achieve rapid protection but give a higher frequency of untoward systemic reactions. Slow schedules are better tolerated but protective doses are only reached after several months (66).…”
Section: Schedules For Venom Immunotherapymentioning
confidence: 99%